Soft skills for the learning achievement of higher level students - Mucha-Huamán, Walter E. (2023)
The objective of this study was to demonstrate the influence of soft skills in the achievement of significant learning of students participating in the Business Process Management course of the Administration specialty at the National Agrarian University of La Selva. The approach was quantitative, applied with an explanatory level and quasi-experimental design with pre and post test. The sample was 42 students and data collection was carried out through the questionnaire and rubric. Inferential analysis was performed using the nonparametric Mann-Whitney U test for independent samples, Student's t test for paired samples, and the Wilcoxon test for paired samples. The results showed that the application of a soft skills program significantly influenced the learning of higher level students; Based on the results found in the general hypothesis test one for related samples and the general hypothesis test two for independent samples, they reflected that the p-value < 0.05 (5%). It is concluded that soft skills influence the acquisition of knowledge of the students analyzed.